Predictive Indicators to Identify High-Risk Paediatric Febrile Neutropenia in Paediatric Oncology Patients in a Middle-Income Country. (15th November 2017) - Green, Lindy-Lee; Goussard, Pierre; van Zyl, Anel; Kidd, Martin; Kruger, Mariana
ABSTRACT: Purpose: To validate a clinical risk prediction score (Ammann score) to predict adverse events (AEs) in paediatric febrile neutropenia (FN). Patients and methods: Patients <16 years of age were enrolled. A risk prediction score (based on haemoglobin ≥ 9 g/dl, white cell count (WCC) < 0.3 G/l, platelet count <50 G/l and chemotherapy more intensive than acute lymphoblastic leukaemia maintenance therapy) was calculated and AEs were documented. Results: In total, 100 FN episodes occurred in 52 patients, male:female ratio was 1.8:1 and median age was 56 months. At reassessment, AEs occurred in 18 of 55 (45%) low-risk FN episodes (score < 9) and 21 of 42 (55%) high-risk episodes (score ≥9) (sensitivity 60%, specificity 65%, positive predictive value 53%, negative predictive value 71%). Total WCC and absolute monocyte count (AMC) were significantly associated with AEs. Conclusion: This study identified total WCC and AMC as significantly associated with AEs but failed to validate the risk prediction score.